2007
DOI: 10.1002/ijc.22567
|View full text |Cite
|
Sign up to set email alerts
|

MIDGE/hNIS vaccination generates antigen‐associated CD8+IFN‐γ+ T cells and enhances protective antitumor immunity

Abstract: Human sodium iodide symporter (hNIS) is a transmembrane protein that actively transports iodide ions into thyroid cells. hNIS is over-expressed in some cases of the thyroid cancers compared with the surrounding normal tissues and has been considered to be an attractive target for immunotherapy. The aim of this study is to determine the feasibility of utilizing the hNIS antigenic protein in enhanced-antigen-associated immunotherapy using image analysis with a gamma counter. To accomplish this, minimalistic immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…These results indicate that Th1 immune responses were depressed in Lewis lung carcinoma, and show that the production of cytokines such as IFN-γ, TNF-α, IL-12, and IL-2 can arrest proliferation of malignant cells and prevent the angiogenesis necessary for tumor growth (3, 5, 17, 21, 22). Similar results were reported in melanoma, liver cancer, and thyroid cancer (22-24). And these phenomena were also confirmed in the titrations of the IgG subclasses.…”
Section: Discussionsupporting
confidence: 88%
“…These results indicate that Th1 immune responses were depressed in Lewis lung carcinoma, and show that the production of cytokines such as IFN-γ, TNF-α, IL-12, and IL-2 can arrest proliferation of malignant cells and prevent the angiogenesis necessary for tumor growth (3, 5, 17, 21, 22). Similar results were reported in melanoma, liver cancer, and thyroid cancer (22-24). And these phenomena were also confirmed in the titrations of the IgG subclasses.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown the presence of auto antibodies against NIS in a subset of autoimmunity induced thyroiditis patients [39] indicating NIS could act as antigen. In mouse tumor models expressing human NIS (hNIS), repeated DNA vaccination with hNIS induced NIS associated CD4 and CD8 T-cell immune response along with improved efficacy [40]. It is likely that at least in mouse tumor models hNIS (86.2% sequence similarity with mouse NIS) [41] could act as foreign antigen and induce hNIS-specific T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The other mechanism, which might be involved, is that the released hNIS itself from dead cells after radionuclide treatment could also raise immune response against viable CNMF cells with hNIS expression. We recently reported that hNIS vaccination with MIDGE plasmid vector could raise hNIS‐associated cell mediated immune responses in mice tumor model 46…”
Section: Discussionmentioning
confidence: 99%